Warisan Sikap Toleran Masa Kesultanan Banjar dan Keberlanjutannya Untuk Masyarakat Lokal Sekarang - Wasita (Kemendikbud, 2020)
The result of this study is intended to prove that the Banjarese have the right attitude of tolerance, supported by archaeological evidences. In this regard, the research question is, how the tolerance implemented by the Banjar community, recorded in archaeological data, and how local people inherit and implement it in their life nowadays? This research used a descriptive method with inductive reasoning. The data were described as well as being placed in the historical timeline of the Banjar Sovereignty. Tolerance data are indicated by the group diversity (at least two groups) existed in the same time and locus, and both have a relationship. Furthermore, tolerance is evidenced by the attitude of the ruler who was willing to tolerate, not suppress, and give proper rights. This study’s results indicate that archaeological evidence had been supported by historical literature, which showed that the Banjar people have strong historical roots of tolerance. The people of South Kalimantan can continue the implementation of that tolerance in a life of diversity presently. It can be concluded that the history of tolerance that has been practiced since our ancestors must be maintained by continuously dialogued so that it can be implemented in an appropriate space and time context.